Rehabilitation staff perspectives on training for problem-solving therapy for primary care in a low vision service. (January 2016) - Sturrock, Bonnie Adele; Holloway, Edith; Keefe, Jill; Hegel, Mark; Casten, Robin; Mellor, David; Rees, Gwyneth
Vision rehabilitation staff were trained to deliver problem-solving therapy for primary care (PST-PC) over the telephone to adults with depressive symptoms and low vision. Training was a 2-day workshop, completion of training cases, and assessment of treatment fidelity. Staff perspectives of training and challenges in PST-PC delivery were explored. Telephone-administered semi-structured interviews were conducted pre- and post-workshop and following PST-PC competency. In all, 14 staff (mean age = 47.64 years, SD = 12.68 years, 93% females) achieved competency and 6 withdrew. Results showed an increased understanding of PST-PC from pre- to post-workshop ( Z = −2.71, p = .007) and pre-workshop to post-competency ( Z = −3.09, p = .002). A high level of satisfaction with training was reported. Staff challenges included the clients' ability to define problems and brainstorm solutions. Training enabled staff to competently deliver PST-PC and may serve as a model for integrating depression care into vision rehabilitation services recommended by international guidelines.